A Review on Mode of Delivery during COVID-19 between December 2019 and April 2020 - Debrabandere, Margot L.; Farabaugh, Dana C.; Giordano, Carolyn (American Journal of Perinatology, 2020)
Objective This study aims to review the published literature to determine mode of delivery in pregnant women with coronavirus disease 2019 (COVID-19) and the indications reported for cesarean section early in the pandemic to add information to the current narrative and raise awareness of trends discovered.Study Design A systematic review was conducted by searching PubMed, Scopus, and ScienceDirect databases for articles published between December 2019 and April 29, 2020 using a combination of the keywords such as COVID-19, coronavirus 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), pregnancy, vaginal delivery, cesarean section, vertical transmission, management, and guidelines. Peer-reviewed case studies with confirmed SARS-CoV-2 women who delivered were included to determine mode of delivery, indications for cesarean section, and maternal and neonatal characteristics.Results A review of 36 total articles revealed deliveries in 203 SARS-CoV-2 positive pregnant women. A comparable severity of disease in pregnant versus nonpregnant women was noted, as previously determined. Overall, 68.9% of women delivered via cesarean section, with COVID-19 status alone being a common indication. Maternal COVID-19 may also be associated with increased risk of preterm labor, although neonatal outcomes were generally favorable. Despite eight of 206 newborns testing positive for SARS-CoV-2, there remains no definitive evidence of vertical transmission.Conclusion COVID-19 status alone became a common indication for cesarean delivery early in the pandemic, despite lack of evidence for vertical transmission. The increase in cesarean rate in this data may reflect obstetricians attempting to serve their patients in the best way possible given the current climate of constantly evolving guidelines on safest mode of delivery for the mother, infant, and provider. Upholding current recommendations from trusted organizations as new data are published, while also providing individualized support to expecting mothers on most appropriate mode of delivery, will reduce the amount of unnecessary, unplanned cesarean sections and could lessen the psychological impact of delivering during the COVID-19 pandemic.Key Points
Keywords: COVID-19; pregnancy; cesarean delivery; vaginal delivery; neonatal outcome; vertical transmission; maternal mental health